Exploration of the gut‐brain axis through metabolomics identifies serum propionic acid associated with higher cognitive decline in older persons. (20th December 2022) - Neuffer, Jeanne; González‐Domínguez, Raúl; Lefèvre‐Arbogast, Sophie; Low, Dorrain Yanwen; Driollet, Bénédicte; Helmer, Catherine; Preez, Andrea Du; de Lucia, Chiara; Ruigrok, Silvie R; Altendorfer, Barbara; Aigner, Ludwig; Lucassen, Paul J.; et al.
Abstract: Background: The microbiome is involved in nutrient metabolism and releases metabolites that can influence cognitive aging, likely through the gut‐brain axis. Human studies, generally limited in number of metabolites and follow‐up, have been inadequate to identify early metabolic alterations leading to cognitive aging. The aim of this study was to investigate the association between circulating levels of a large number of microbial metabolites in plasma and cognitive decline. Methods: We studied participants from the Three‐City study, a cohort study conducted in 3 French cities (Bordeaux, Dijon ad Montpellier). The subjects were free of dementia at the time of blood sampling and provided repeated measures of cognition over 12 subsequent years. We used a targeted metabolomic approach, combining ultra‐high performance liquid chromatography coupled to tandem mass spectrometry. We measured 77 circulating gut‐derived metabolites in a case‐control sample matched for age, sex and educational level, nested within the cohort. Associations of these metabolites to cognitive decline were investigated in the Bordeaux center (discovery sample, n = 418) using logistic regressions conditioned on matching variables. Associations with a P‐value corrected for multiple testing (False Discovery Rate [FDR]) ≤0.15 were tested for validation in the Dijon center (validation sample, n = 424). Models were subsequently adjusted for smoking, alcohol consumption and cardiometabolic health (body mass index, hypertension, hypercholesterolemia and diabetes). Results: Higher serum levels of propionic acid, a short‐chain fatty acid, were associated with increased odds of cognitive decline (OR for 1 SD = 1.40 [95% CI 1.11, 1.75] in discovery, and = 1.26 [1.02, 1.55] in the validation stage). Associations were attenuated in the validation sample after multivariable adjustment, and additional analyses suggested mediation by hypercholesterolemia and diabetes. Moreover, propionic acid strongly correlated with blood glucose (r = 0.80) and with meat and cheese intakes (r>0.15) but not with fiber intake (r = 0.04). Conclusion: This exploratory study of the gut‐brain axis suggests a deleterious relationship between circulating propionic acid and cognitive decline. Our results suggest a very weak relation to pre‐biotic foods, but a possible link with processed foods, where propionic acid is often used as a preservative. Thus, the adverse impact of propionic acid on metabolism and cognition deserves further investigation.